2004
DOI: 10.1063/1.1843281
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic growth of group III-nitride nanowires and nanostructures by metalorganic chemical vapor deposition

Abstract: We report flexible synthesis of group III–nitride nanowires and nanostructures by metalorganic chemical vapor deposition (MOCVD) via a catalytic vapor-liquid-solid (VLS) growth mechanism. Supersaturation and surface stoichiometry strongly influence the stability of liquid droplets and growth selectivity. To facilitate and sustain the VLS growth, indium catalyst is introduced based on thermodynamic consideration. The employment of mesoporous molecular sieves (MCM-41) helps to prevent the coalescence of catalyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 23 publications
0
41
0
Order By: Relevance
“…GaN and InN nanowires have been prepared by various techniques including plasma-assisted molecular beam epitaxy [5], laser ablation [6], metal organic chemical vapour deposition [7] and reaction of NH 3 with Ga [3,4] (In [8]) powder, Ga/GaN [2] or Ga/Ga 2 O 3 [9] (In/In 2 O 3 [10]) mixtures. In contrary, little is reported on the preparation of AlN nanowires [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…GaN and InN nanowires have been prepared by various techniques including plasma-assisted molecular beam epitaxy [5], laser ablation [6], metal organic chemical vapour deposition [7] and reaction of NH 3 with Ga [3,4] (In [8]) powder, Ga/GaN [2] or Ga/Ga 2 O 3 [9] (In/In 2 O 3 [10]) mixtures. In contrary, little is reported on the preparation of AlN nanowires [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Also, it was found that the nanowires had a uniform single-crystalline core surrounded by an amorphous coating. On the other hand, by employing In as a catalyst to assist the VLS growth, Su et al [41] had synthesized AlN nanowires through metal-organic chemical vapor deposition. From their observations, the group concluded that the stability of the liquid droplets and the selectivity in the VLS growth process relied very much on the supersaturation level and surface stoichiometry.…”
Section: Catalyst-assisted Vls Growth Methodsmentioning
confidence: 99%
“…Various fabrication methods have been employed to synthesize these nanowires and they may be classified into four main classes: (1) template-confined method [16,[31][32][33], (2) direct current (DC) arc discharge method [34][35][36][37][38], (3) catalyst-assisted vapor-liquid-solid (VLS) growth method [39][40][41][42][43][44][45][46], and (4) catalyst-free vapor-solid (VS) growth method [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63]. Although significant progress in the synthesis of AlN nanowires has been achieved lately, some challenges remain and are expected to be overcome in the near future.…”
Section: Introduction and Background Of Aluminum Nitride (Aln) Nanowiresmentioning
confidence: 99%
“…Synthesis of wide bandgap GaN NWs has been reported on a variety of substrates, including alumina [3,4], quartz [5], silicon dioxide [6], silicon (111) [7], and c-face sapphire; morphology of haystack-like, random-oriented GaN NWs are commonly observed. These NWs are typically processed into devices through solution sonication and dispersion unto target wafers before electrically contacted by metallization.…”
Section: Introductionmentioning
confidence: 98%